King Taufu Corner (KTC) / Mohd Ezwan Masdar ... [et al.] - Masdar, Mohd Ezwan; Ilias, Hayati; Baharuddin, Kamal Izwan; Ali, Rizal; Mohd Natar, Abd Hafiz; Md Saad, Nuuraini (Faculty of Art and Design, 2003)
After all the research and observation on the other business nowadays, we have decided to named our Cafe as King Taufu Corner ( KTC ) because it appropriate with our goals to introduce to the customers the choice of variety type of Yong Taufu and food base on tauhu to replace old habits like others fast food businesses with nutritious and good tasting recipes. The form of our business is partnership of six person which each partner play an important roles to establish this business. The location of our Cafe is in Ground Floor ( G 39 ), Plaza Alam Sentral, Shah Alam, Selangor.